2008
DOI: 10.1095/biolreprod.107.065433
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-Mediated Migration of Human Trophoblast Requires RAC1 and CDC421

Abstract: The invasion of maternal decidua and uterine spiral arteries by a trophoblast subpopulation called extravillous trophoblast (EVT) is essential for the establishment of a normal placenta and an adequate blood flow toward the fetus. Derangements in these processes underlie pregnancy-related diseases like preeclampsia and intrauterine growth restriction. Many growth factors, growth factor binding proteins, and extracellular matrix components can positively or negatively regulate the proliferation, migration, and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 64 publications
3
30
0
Order By: Relevance
“…It is notable that knockdown of both Cdc42 and Rac1 is necessary to completely abolish the response to leucine deprivation. Similar data have been reported for other models (17,62). For example, epidermal growth factor activates both Rac1 and Cdc42 in a synergistic manner to regulate the downstream pathway (50).…”
Section: Discussionsupporting
confidence: 86%
“…It is notable that knockdown of both Cdc42 and Rac1 is necessary to completely abolish the response to leucine deprivation. Similar data have been reported for other models (17,62). For example, epidermal growth factor activates both Rac1 and Cdc42 in a synergistic manner to regulate the downstream pathway (50).…”
Section: Discussionsupporting
confidence: 86%
“…Compared to normal pregnancy tissues, our research discovered that Rac1 expression declined in preeclampsia placental tissues. This evidence, along with the previous observation that Rac1 activity was significantly lower in women with preeclampsia and HELLP [6][7][8], supports the view that Rac1 potentially contributes to placental development. Furthermore, the present study showed the activity of Rac1 at different gestational stages and under preeclampsia conditions; these changes corresponded with the down-regulation of trophoblast invasion, suggesting that Rac1 may be involved in the regulation of trophoblast invasion to prevent shallow placental implantation.…”
Section: Discussionsupporting
confidence: 85%
“…Studies have also shown that the activity of Rac1 is downregulated in preeclampsia and HELLP syndrome [6], suggesting a potential contribution of Rac1 to placental development. Moreover, the activation of PTGER1 and PTGER4 which serve as mediators of the PGE 2 -induced migration of first trimester human EVTs can activate Rac1 [7]. A recent study indicated that RhoGDI2, which belongs to a family of Rho guanosine diphosphate dissociation inhibitors, suppressed EVT migration by inhibiting the activation of Rac1 [8].…”
Section: Rac1/β-catenin Signalling Pathway Contributes To Trophoblastmentioning
confidence: 99%
“…Note that SMAD genes belong to both the Wnt and the TGFβ signaling pathways. Interestingly, RAC1 was reported to regulate several reproductive events, including embryo implantation (Grewal et al, 2008;Nicola et al, 2008), meiotic spindle stability and anchoring in mammalian oocytes (Halet and Carroll, 2007), and embryonic epithelial morphogenesis (He et al, 2010). In addition, RAC1 can stimulate STAT3 activation and therefore affect the transcription of many genes (Faruqi et al, 2001;Park et al, 2004;Kawashima et al, 2006).…”
Section: Pituitary Gland Genes: Differentially Expressed and Interactingmentioning
confidence: 99%